2021
DOI: 10.1073/pnas.2014346118
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-induced pH shifts link individual cell physiology to macroscale collective behavior

Abstract: Bacteria have evolved a diverse array of signaling pathways that enable them to quickly respond to environmental changes. Understanding how these pathways reflect environmental conditions and produce an orchestrated response is an ongoing challenge. Herein, we present a role for collective modifications of environmental pH carried out by microbial colonies living on a surface. We show that by collectively adjusting the local pH value, Paenibacillus spp., specifically, regulate their swarming motility. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Similarly, plants could act as mediators and connect microbial metapopulations via VOCs, potentially leading to VOC-mediated interdependences and metarhizobiome stability at the landscape level, highlighting the importance of Gamma diversity. For example, Dharanishanthi et al ( 69 ) reported that modification of the environmental pH by neighboring bacterial species could be used as a clue about nutrient availability by local bacteria, linking individual bacterial physiology to macroscale collective behavior.…”
Section: Metarhizobiome: Linking Microbial Metapopulation Network With Plantsmentioning
confidence: 99%
“…Similarly, plants could act as mediators and connect microbial metapopulations via VOCs, potentially leading to VOC-mediated interdependences and metarhizobiome stability at the landscape level, highlighting the importance of Gamma diversity. For example, Dharanishanthi et al ( 69 ) reported that modification of the environmental pH by neighboring bacterial species could be used as a clue about nutrient availability by local bacteria, linking individual bacterial physiology to macroscale collective behavior.…”
Section: Metarhizobiome: Linking Microbial Metapopulation Network With Plantsmentioning
confidence: 99%
“…S13 ). This phenomenon has been observed in other bacteria that secrete organic acids from glucose metabolism, such as lactic, acetic, succinic, and pyruvic acid, causing rapid extinction of the entire population due to the lowered pH of the environment [ 14 , 15 , 56 , 77 79 ]. In contrast, DT-2, with a defective hexokinase and phosphotransferase system, efficiently utilizes pyruvic acid as a carbon source (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…S22). These observations suggest that many Bacillus species may have the ability to generate pyruvic acid from glucose, thereby acidifing their growth environment [15,[56][57][58][59]. These bacteria also arsM gene in their genomes, which enables the methylation of MAs(III).…”
Section: Mas(iii)mentioning
confidence: 99%
“…11 In addition, bacteria within a clonal population can coordinate individual behaviors to achieve collective behaviors, such as collective growth and migration. [101][102][103] In order to understand how such heterogeneity and coordination affect population growth, it is critical to measure quantities (such as metabolic states) at the singlecell level within the colony. 100,104 Such measurements allow quantification of the heterogeneity among individual cells and a link to be made between individual-level behaviors and processes at the level of the population.…”
Section: Two-dimensional Microcolonies Interacting With the Environme...mentioning
confidence: 99%